Tensions in Co-teaching Practices during the Implementation of Bilingual Intercultural Education - Arias Ortega, Katerin Elizabeth (2022)
The article exhibits professional tensions in co-teaching practices among the educational actors in charge of implementing the Bilingual Intercultural Education Program (PEIB) in indigenous contexts of Chile. Through the investigation, the authors realized the contributions and limitations of their professional work in the materialization of the PEIB. The theoretical framework that supports the study is the co-teaching approach in school education, which implies collaborative teaching between professionals who transmit indigenous knowledge and knowledge of their own language and culture at school.  Regarding the methodology, the authors chose a qualitative one; moreover, they conducted semi-directed interviews with four pedagogical pairs in charge of implementing the PEIB in the school. The information analysis technique is carried out from a content analysis of their testimonies in which the explicit and latent meanings that they transmit through it are identified. This is triangulated with the information that emerges from the process of open and axial coding of their testimonies, from the grounded theory. The main results show a limited professional performance characterized by a lack of planning, design and evaluation of their own pedagogical and didactic work to teach the indigenous language and culture in the classroom. Likewise, the investigators found a lack of spaces for planning and coordination between co-teachers, which limits an adequate implementation of the PEIB. The main conclusions highlight the urgency of focusing improvement efforts on four aspects: (a) clarity of roles and functions of co-teachers, (b) collaborative work between co-teachers, (c) institutional and educational community support for the teaching of indigenous language and culture in the classroom and, (d) intercultural training of co-teachers to reverse prejudice and stigmatization towards indigenous children, their families and therefore towards the PEIB.